«Cognitus & Moi»: A Computer-Based Cognitive Remediation Program for Children with Intellectual Disability - Demily, Caroline; Rigard, Caroline; Peyroux, Elodie; Chesnoy-Servanin, Gabrielle; Morel, Aurore; Franck, Nicolas (Frontiers in Psychiatry, 2016)
Attentional, visuospatial and social cognition deficits have a negative impact on children’s adaptative and social competences and, as a result, on their ability to achieve a normal functioning and behavior. Until now and despite the frequency of those deficits, there is a lack of children’s specific cognitive remediation tools specifically dedicated to attentional and visuospatial areas. The « Cognitus & Moi » program involves a variety of exercises in a paper and/or pencil (n=30) or a computerized format (n=29) and a strategy coaching approach. Each module of « Cognitus & Moi » targets a single impaired cognitive area, within the limits of cognitive domains' overlapping. The little cartoon character named Cognitus, who illustrates the program, is supposed to be very friendly and kind towards children. Cognitus will accompany them throughout the program for an effective and positive reinforcement. The main goal of « Cognitus & Moi » is to adjust to children’s difficulties in daily life. Moreover, since the cognitive remediation benefit is complex to apply in daily life, the program is based on a metacognitive strategy. After a complete neuropsychological assessment and a psychoeducational session (with the child and the parents), 16 one hour-sessions of cognitive remediation with the therapist are proposed. Each session is composed of three parts: (1) computerized tasks focusing on specific attentional or visuo-spatial components (20 minutes). The attentional module targets hearing, visual and divided attention. A double attention task is also proposed. The visuo-spatial module targets eye tracking and gaze direction, spatial orientation, visuo-spatial memory and construction, and mental imagery. (2) pen and paper tasks focusing on the same processes (20 minutes) and a facial emotion recognition task. (3) a proposal of a home-based task (during 20 minutes). Weekly, specific attentional and visuo-spatial home tasks are proposed to the child and analyzed with the parents and the therapist. Indeed, home exercises are useful to promote the transfer of strategies to daily life and their subsequent automation. The heterogeneity of cognitive deficits in intellectual deficiency necessitates an individualized cognitive remediation therapy. In this regard, « Cognitus & Moi » seems to be a promising tool.